Does instructional time at school influence study time at university? Evidence from an instructional time reform - Schwerter, Jakob; Netz, Nicolai; Hübner, Nicolas (Technische Universität Dortmund, 2024)
Early-life environments can have long-lasting effects on individuals’ later life courses. Interestingly, research on the effects of school reforms has hardly adopted this perspective. Therefore, we investigate a staggered school reform that reduced the number of school years and increased weekly instructional time for secondary school students in most German federal states. We analyze this quasi-experiment in a difference-in-differences framework using nationally representative large-scale survey data on 69,513 students who attended university between 1998 and 2016. Using both TWFE and weighted-group ATT estimators, we find negative effects of reform exposure on hours spent attending classes and on self-study. Moreover, reform exposure increased the time gap between school completion and higher education entry. Our results support the view that research should examine unintended long-term effects of school reforms on individual life courses.
Economics of education review; 100
Keywords: G8 high school reform; Higher education; Study time; Long-term effect; Staggered difference-in-differences; 370; Schulreform; Bildungspolitik; Hochschule; Sekundarstufe